99.7k views
1 vote
!!!HELP!!!

Determine the equation that will shift the polynomial p(x) = (x - 2)2(x + 5) up 3 units and left 4 units.

A g(x) = (x + 1)2(x + 8) - 4
B g(x) = (x + 1)2(x+4)
C g(x) = (x + 2)2(X + 9) + 3
D g(x) = (x - 6)2(x + 1) + 3

!!!HELP!!! Determine the equation that will shift the polynomial p(x) = (x - 2)2(x-example-1

1 Answer

4 votes

Answer:

D

Explanation:

you have to replace x by x-4 and add 3

(x-4-2)^2(x-4+5)+3=(x-6)^2(x+1)+3

User Lahiru Amarathunge
by
5.3k points